Prevalent Complications Following Spinal Anaesthesia in Perioperative Clinical Practice: A Scoping Review - Indriani, Ria; Solichah, Nur Umi Aminatus; Setyawati, Anita (Universitas Padjadjaran, 2026)
Spinal anesthesia is among the most often employed regional anaesthetic procedures in perioperative clinical practice. Notwithstanding its multiple benefits, including swift onset of action and effective pain management, this approach remains associated with the potential for post-procedural problems that may affect patient recovery and the quality of anesthesia care. This study aimed to delineate the numerous common problems that arise following spinal anesthesia in adults, utilising findings from current studies via a scoping review methodology. This research employed a scoping review methodology in accordance with the PRISMA-ScR criteria. Fifteen articles were retrieved from the PubMed, Scopus, and Garuda databases utilising pertinent keywords within the publication period of 2020–2025. The inclusion criteria comprised full-text papers authored in either Indonesian or English that addressed issues following spinal anesthesia. Fifteen publications were selected and analysed according to their objectives, methodologies, populations, and findings. The research identified that the most commonly reported problems comprised hypotension, bradycardia, post-dural puncture headache, nausea, shivering, urine retention, and modest neurological sequelae. Factors influencing the occurrence of problems encompass gender, age, hydration condition, technique, and the utilisation of spinal needles. The majority of issues are temporary and can be addressed with supportive or pharmaceutical measures. Complications following spinal anesthesia are prevalent and should be anticipated in the practice of anaesthesiology nursing. A comprehensive grasp of problem types and their associated risk factors might enhance nurse anaesthetists’ efficacy in monitoring, patient education, and post-anesthesia treatment. This study underscores the necessity of enhancing clinical practice standards and education to reduce adverse occurrences